Dynamic numerical simulations of dry-stone retaining walls: identification of the seismic behaviour factor - Savalle, Nathanaël (2022)
Dry-stone retaining walls can be found worldwide and constitute critical assets of the built heritage for many sloped territories, holding cultural and economic value. Their design currently follows empirical rules, though the first steps towards a static safety assessment have recently been proposed in the scientific and engineering literature. However, the seismic design of these structures still lacks research studies. Therefore, this work conducts discrete element simulations to assess their dynamic behaviour. First, the approach is validated through existing scaled-down shaking table experiments, and it is found that the numerical simulations are conservative (i.e., on the safe side). Next, full-scale dry-stone retaining walls are subjected to harmonic excitations as an idealisation of earthquakes. Finally, based on a simplified limit-equilibrium analytical tool, their seismic behaviour factor is estimated for the first time in the literature, which falls within the proposed values of the European standards (Eurocode 8). This will allow engineers to adopt a validated behaviour factor in practice to assess and design dry-stone retaining walls with a pseudo-static approach.